2014
DOI: 10.1016/j.jhtm.2014.08.003
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of Australian and New Zealand hotel ownership

Abstract: The results of a study seeking to advance a typology of hotel owners as well as examining the composition of hotel owners in Australia and New Zealand are reported. Interview observations resulted in the six hotel ownership categories, discernible from prior commentaries, being broadened to nine hotel owner types. Considerable insights with respect to differentials in the investment time horizon and capital expenditure strategy applied by different owner types were gleaned from the interview data. From a quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…It is important to recognize that hotel owners do not have the same investment time horizon, opportunities, funds or investment goals. Turner and Guilding (2014) highlighted that hotel owners’ investment time horizons range from short-sighted (5 years or less) to long-term (10 or more years). Owners with a short investment time horizon, categorized as being “opportunity funds” (e.g., Morgan Stanley), are typically characterized by a strategy of “buy low and sell high.” Capital investment decisions for this class of owners are more tactical than strategic (Davis & deRoos, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to recognize that hotel owners do not have the same investment time horizon, opportunities, funds or investment goals. Turner and Guilding (2014) highlighted that hotel owners’ investment time horizons range from short-sighted (5 years or less) to long-term (10 or more years). Owners with a short investment time horizon, categorized as being “opportunity funds” (e.g., Morgan Stanley), are typically characterized by a strategy of “buy low and sell high.” Capital investment decisions for this class of owners are more tactical than strategic (Davis & deRoos, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…do whatever they do, get out in a three to five-year period, take the profit and go. These guys are not interested in maintaining the long-term integrity of the hotel.” (Turner & Guilding, 2014, p. 79)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large proportion of owners of publicly traded hotel companies are institutional in nature (Turner & Guilding, 2014), a factor that might reasonably be expected to promote a culture of more formalised and financially oriented capital budgeting decision making.…”
Section: Public Versus Private Hotel Ownershipmentioning
confidence: 99%
“…This is particularly the case when it is recognised that it is the owner that generally funds most hotel capital expenditure. Furthermore, different types of hotel owner do often vary considerably in terms of their size and this size can therefore have a significant impact on the capital budgeting strategies that they adopt (see Turner & Guilding, 2014). Little empirical academic research was found, however, that had attempted to measure the size of a hotel owner.…”
Section: Hotel Owner Sizementioning
confidence: 99%